Transforming Accounting Education Through Educators Consciousness: A Theatrical Perspective - Kamayanti, Ari (Journal of Accounting Research, Organization and Economics, 2018)
AbstractObjective Study aims to portrait how changes in accounting education should start with ac-counting educators consciousness and how to trigger this consciousness.Design/methodology This study offers alternative perspective to enhance accounting education through educators consciousness. This study took place in ACURA that was established in May 1986 in Surabaya by a group of public state university lecturers. By employing a qualitative approach namely dramaturgical interventionism study in a private university, the changes of accounting lecturers consciousness were observed and presented.Results It is found that educators consciousness is necessary to change the course of accounting education to be geared for civilization. The most important trait that an accounting education has is a continuously critically conscious (3C) character. However, the critical consciousness is only part that will make up self consciousness.Research limitations/implications This findings could be transferrable to other institutions with similar context. This also opens up another door to further research, especially one that is applicative in nature.